Nitric oxide formation during corn straw/sewage sludge co-pyrolysis/gasification. (1st October 2018) - Chen, Guanyi; Yang, Ruilei; Cheng, Zhanjun; Yan, Beibei; Ma, Wenchao
Abstract: Nitric oxide formation in accompanying with biomass-derived gas during pyrolysis/gasification would contribute to around 15% of nitrogen oxide emission during subsequence combustion. In this work, in order to meet the increasingly stringent nitrogen oxide emission regulation, nitric oxide emission characteristics during co-pyrolysis/gasification of corn straw and sewage sludge were investigated in a laboratory-scale tubular furnace. Results showed that nitric oxide formation was noticeably occurring, and the synergistic effect was existed during corn straw/sewage sludge co-pyrolysis. The sewage sludge proportion of 75 wt% caused 25.3% nitric oxide reduction, double the figure for 50 wt% sewage sludge and 25 wt% sewage sludge (12.5% for 50 wt% sewage sludge and 13.2% for 25 wt% sewage sludge). During co-pyrolysis, nitric oxide emission was affected by different parameters. Heating rate could affect nitric oxide emission through a comprehensive mechanism which contented the effect on reaction time, nitric oxide reduction by carbon monoxide on char surface, and the effect on the devolatilization strength. Hydrogen/nitrogen ratio could also affect nitric oxide emission, however, the influence degree decreased as hydrogen/nitrogen increased. Furthermore, the oxygen/nitrogen ratio in fuel blends was determined as the most critical parameter on nitric oxide emission through Grey Relational Analysis. During co-gasification, Nitrogen functional groups were determined by Fourier Transform infrared spectroscopy. Char residues in 5%Oxygen/95%Argon atmosphere showed more functional groups related to N-containing matters than that in 5% Carbon dioxide/95%Argon, especially Amide group (CarbonNitrogen bond amide III, CarbonOxygen double bonds amide I) and NitrogenHydrogen bond remained. And this result indicated that different atmospheres could affect nitric oxide emission through the pathway of the fuel-nitrogen transformation.1.